A Review of Strategies to Implement Sustainable Urban Transportation Options in Malaysia (Jurnal Teknologi (Sciences & Engineering), 2014)
Since the 1987 Brundtland Commission report brought global attention to sustainable development, many scholars and professionals have worked to apply its principles, notions and strategies in the urban context to transportation. Consequently, this paper examines strategies to implement sustainable transport. It traces efforts to operationalize the notion of sustainable road transportation in transport options. The authors address the problem faced by the Malaysian transportation sector today in major economic, social and environmental elements. Then, the authors identify various strategies that focused on improvement such as Non-Motorized Transport (NMT), Public Transport and Private Vehicles. The authors also discuss extending all strategies comprising these three parts. This paper calls for further studies to verify the best strategies to implement, given that some strategies may be suitable or convenient at certain places and under certain circumstances.